The Effects of Economic Crisis on Business Finance - Lesi Hertati; Marlina Widiyanti; Desfitrina Desfitrina; Afriapollo Syafarudin; Otniel Safkaur (International Journal of Economics and Financial Issues, 2020)
A crisis is a period associated with events that occur unexpectedly that have a negative impact on the organization. The economic crisis is caused by an unforeseen world situation so it must provide a fast, precise and accurate decision so as not to affect the organization's overall operations as a bold step to minimize unintended consequences. A crisis is an event that can destroy an organization and its employees, products, services, and the financial condition of a business enterprise like a corona outbreak. An economic crisis if left unchecked can cause a financial situation that is a concern, a crisis which is an event that has a broad scope of society. The crisis has the potential to cause long-term damage to the financial image of a business company will lose public trust in consumer confidence can weaken the morale of company employees who are experiencing a crisis, can pose the risk of increasing the intensity of the problem. Thus, the aim of this paper is to examine the effects of economic crisis on buriness finance. The data analysis technique uses the structural equation modeling technique, which involved 400 Indonesian small and medium entrepreneurs and 162 samples collected on employees. The results show that the effect of the economic crisis on the financial statements of Indonesian medium and small micro traders plays an important role in the economic crisis so that business finance business is very influential when there is uncertainty in the environment, the financial statements of small and micro business enterprises sweeping across the globe hit making bad changes in the financial statements of micro and small business entrepreneurs in Indonesia. This research was conducted on micro small and medium entrepreneurs in Indonesia.